Paleobiologia de Corumbella werneri (Ediacarano, Grupo Corumbá): implicações paleoecológicas e evolutivas - Sampaio, Guilherme (Universidade Federal de São Carlos, 2018)
The Edicaran period (635-541 Ma) was characterized by great changes on the planet, among them, important modifications on the biosphere. In this time interval there was a diversification of unicellular Eucarya, including their macroscopic forms. A representative of the Ediacara-Cambrian boundary is the fossil Corumbella werneri, scyphozoa, firstly described in the pellets of the Tamengo Formation. Corumbella werneri might have been one of the first animals capable of synthetising hard-parts, in a context in which active predation was still being stablished. Due to this, the work here presented, had as objectives: (1) to verify mineralogical and chemical composition of the carapace of Corumbella; (2) to investigate palaeoecological aspects of this organism; (3) To narrow the evolutionary affinities; (4) to ascertain the existence of other taxa associated. For this, it was used non-destructive techniques, such as MicroCT and spectroscopy, allied with petrography. Different intensities of calcite and kerogen were verified on the carapace of Corumbella, indicating a possibility of an organo-mineralized skeleton. Data about the taxonomy of Corumbella revealed that it is a sister-group of conulariids. As for the other components of the paleobiota of Tamengo Formation, microfossil studies showed ovoids structures and acritarches. These ovoids structures have been found associated with Corumbella specimens, and have been interpreted as a result of the interaction between microbial mats and the substract. For the acantomorphic acritarches, here described for the first time in a new locality of Tamengo Formation. They were characterized, mostly, as Bavlinella sp e Leiosphaeridia spp.. In an important way, the identification of acritarches strengthens biostratigraphic studies, which might stablish biozones for the Late Ediacara, in this unit. Therefore, this work presents new data which contribute both for the general knowledge about paleoecology and taxonomy, and generates new insights and questions that might be answered in future studies.
Keywords: Assembleia Nama; Biomineralização; Biota de Ediacara; Esqueletogênese; Formação Tamengo; Nama assemblage; Biomineralization; Ediacaran biota; Skeletonization; Tamengo Formation; CIENCIAS BIOLOGICAS::ECOLOGIA